Hard alloy end mill structure applicability evaluation method based on cutter material degradation

Through the evaluation method of structural applicability of cemented carbide end mills based on tool material degradation, the problem of tool structure optimization relying on a large number of cutting experiments is solved, and the effect of reducing experiment volume and cost is achieved, and the service life and cutting efficiency of the tool are improved.

CN119885724APending Publication Date: 2025-04-25NANJING INST OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411881507.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The structural optimization of tools mainly relies on a large number of cutting experiments, which requires a large amount of tool and workpiece materials to be consumed, which is relatively expensive.

Method used

A method for evaluating the suitability of carbide end mill structure based on tool material degradation is provided. By measuring and calculating the parameters of tool material, the suitability of tool structure is evaluated and the amount of experiment is reduced.

Benefits of technology

The rationality and applicability of the tool structure are evaluated through numerical calculations, which reduces the amount of experiments, reduces the cost, provides quantifiable results, and improves the tool's service life and cutting efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119885724A_ABST
    Figure CN119885724A_ABST
Patent Text Reader

Abstract

The invention discloses a hard alloy end mill structure applicability evaluation method based on cutter material degradation. The hard alloy end mill structure applicability evaluation method comprises the following steps that the microstructure, material parameters and high-temperature performance of WC-Co hard alloy are identified; establishing a relation model of the cutter material performance and the degradation factor, and obtaining a relation between cutter material degradation and a cutting effective stress component in combination with an ideal stress component of a cutter material unit calculated by a finite element; and according to the end mills with different structural parameters, calculating the modified equivalent stress # imgabs0 # considering the material performance degradation to evaluate the cutting service life of the cutter, and taking the cutting service life as an index for judging the structural applicability of the cutter. The method has the advantages that the rationality of the tool structure can be evaluated through the mechanical parameters and the cutting conditions of the tool material, the cutting experiment amount is effectively reduced, a quantifiable result is provided in the aspect of optimizing the tool structure, and an effective method is provided for improving the performance of the cutting tool.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cutting tool structure design and optimization, and relates to a method for evaluating the structural applicability of a cemented carbide end mill based on tool material degradation. Background Art

[0002] The industry continues to push the limits of material performance, moving towards low machinability and high strength, which poses a huge challenge to cutting tool performance. With the growing demand for high-performance cutting tools in modern manufacturing, optimizing tool performance has become critical. This requires a deep understanding of the interaction between tool material microstructure, mechanical properties and structural parameters, and accurate judgment of the rationality and applicability of tool structural parameters.

[0003] The methods to improve tool performance mainly focus on improving tool material properties, manufacturing processes, and optimizing tool geometry. Among them, a reasonable tool structure is the basis for improving cutting performance, reducing cutting forces, and increasing tool life. At present, the structural optimization of tools mainly relies on a large number of cutting experiments, and rarely combines the performance changes of tool materials with the applicability and matching of tool structure parameters, which means that a large amount of tool and workpiece materials are consumed, which is costly. Therefore, it is necessary to integrate the parameter variables such as tool material microstructure, performance, and tool structure, clarify the complex relationship between the behavior of tool materials at high temperatures and tool structure, evaluate the performance degradation of tool materials in the actual cutting process, and then evaluate the applicability of tool structure to improve tool life and cutting efficiency. Summary of the invention

[0004] 1. Technical problems to be solved:

[0005] The structural optimization of the tool mainly relies on a large number of cutting experiments, which requires a large amount of tool and workpiece materials and is costly.

[0006] 2. Technical solution:

[0007] In order to solve the above problems, the present invention provides a method for evaluating the structural applicability of a cemented carbide end mill based on tool material degradation, comprising the following steps:

[0008] Step S01: prepare a cemented carbide sample and measure the elastic modulus, Poisson's ratio, porosity, grain size, and friction coefficient material parameters of the tool material.

[0009] Step S02: Calculate the three-point bending elastic modulus; calculate the three-point bending elastic modulus of the cemented carbide sample at high temperature; perform three-point bending tests on the cemented carbide sample at room temperature and high temperature respectively, obtain the load and deflection before the sample breaks, and calculate the three-point bending elastic modulus of the tool material by the following formula:

[0010]

[0011] Where L is the span of the specimen, F is the applied load, δ is the deflection of the specimen, and I is the bending moment of the specimen (I = bh 3 / 12, b is the width of the sample, h is the height of the sample.

[0012] Step S03: Calculate the degradation factor D of the cemented carbide tool material.

[0013] Step S04: Considering the degradation of the tool material, calculate the effective stress component of the tool surface during cutting Equivalent stress

[0014] Step S05: Design carbide end mills with different structural parameters and calculate the equivalent stress of different structural tools during cutting The evaluation index of the tool structure is obtained to evaluate the applicability of the tool structure.

[0015] Step S06: Verify the correctness of the tool structure applicability evaluation method described in the above steps.

[0016] In step S01, the surface of the WC-Co cemented carbide is polished and observed by a scanning electron microscope (SEM). According to the SEM image of the microstructure, the grain size within the material unit size is measured and the average grain size is calculated.

[0017] In step S03, the relationship between tool cutting stress and tool material degradation is established. The influence of microstructure on tool material performance is represented by a continuous internal field, and the stress tensor of the material unit is:

[0018] σ=E(1-D)ε

[0019] Among them, ε is the elastic strain of the material unit, E is the Young's modulus of the material, and D is the degradation factor.

[0020] When the tool material unit is subjected to compressive stresses σ1 and σ2, the axial and lateral strains ε1 and ε2 are:

[0021]

[0022] Among them, ε1 e and ε2 e is the elastic strain of the ideal material unit, ε1 d and ε2 d is the inelastic strain caused by microcrack growth, v is Poisson’s ratio, k = [(3-v) / (1+v)], M 11 、M 12 、M 21 and M 22is a constant term, N = 4hbP / c 2 , P is the porosity, c=0.5d, d is the grain size of the material.

[0023] Under axial load pressure, the above formula is simplified to:

[0024]

[0025] Constant M 11 and M 12 for:

[0026]

[0027] Where l is the crack extension length, θ = π / 4, w = 4c, μ is the friction coefficient, l * =0.27c,l ** =0.083c.

[0028] Substitute the tool material parameters obtained in step S01 into the following formula to calculate the initial degradation factor: D I :

[0029]

[0030] Where N is the number of cracks, N = 4hbP / c 2 ; P is porosity, E u =E / (1-2v);M 11 、M 12 is a constant term, including the Poisson's ratio, porosity, grain size, and friction coefficient parameters of the tool material.

[0031] Establishment of high temperature degradation factor D H The relationship between the high temperature degradation factor D and the cutting temperature T is calculated by substituting the three-point bending elastic modulus obtained by Xing Hong in step S02 into the following formula: H :

[0032]

[0033] Among them, E b is the three-point bending elastic modulus of cemented carbide at room temperature, is the three-point bending elastic modulus of cemented carbide at different high temperatures; the high temperature degradation factor D is plotted H Relationship diagram with cutting temperature T, high temperature degradation factor D is obtained by least square method H Mathematical relationship with temperature T:

[0034] D H =f(T).

[0035] According to the initial degradation factor D I and high temperature degradation factor DH , the degradation factor of cemented carbide tool material is obtained by the following formula:

[0036] D=1-(1-D I )(1-D H ).

[0037] In step S04, the effective stress component of the tool surface cutting is calculated by combining the degradation factor D of the tool material with the following formula: Equivalent stress

[0038]

[0039] in, is the equivalent stress, is the effective stress component, σ ij is the ideal stress component, D is the degradation factor, h = 0.2, v is the Poisson's ratio, δ ij is the Kronecker symbol, is the hydrostatic stress, are matrices with the same subscripts as in the stress components.

[0040] Ideal stress component σ ij The results are obtained by finite element method, as follows: the finite element software AdvantEdgeFEM is used to calculate the cutting process. The workpiece material is titanium alloy TC4, the tool material is WC-Co cemented carbide, and the tool is a 2-edge cemented carbide integral end mill. When the cutting edge achieves a complete cutting-in and cutting-out process, the cutting temperature T and the ideal stress component σ are extracted in the rake face and flank face areas. ij .

[0041] In step S05, the side edge rake angle γ is selected. s 、 Side edge clearance angle α s , End edge rake angle γ e and helix angle β as tool structure parameters, design four factors and four levels L 16 (4 5 ) Orthogonal table, equivalent stress on the rake face and flank face of the tool cutting area Perform calculations.

[0042] The parameters used in the calculation are: 2-edge carbide solid end mill, diameter 5mm, cutting speed 300m / min, feed per tooth 0.02mm / z, axial cutting depth 0.2mm and radial cutting depth 2.5mm.

[0043] In step S06, the preferred tool structure obtained in step S05 is selected and the cutting life is compared with other tools with different structural parameters. The cutting test parameters are the same as the calculation parameters. After cutting for a certain period of time, the wear width of the back tool surface is measured. When the back tool surface is severely worn or the tool is chipped, the experiment is stopped and the tool life of the tool is calculated.

[0044] 3. Beneficial effects:

[0045] The present invention evaluates the rationality and applicability of the tool structure through numerical calculation, which makes up for the shortcomings of the empirical method and the experimental method, greatly reduces the amount of experiments, and provides quantifiable results in optimizing the tool structure and performance. The mechanical parameters and performance degradation of the tool are tested at the tool material sample stage, and no cutting experiment is required, which can effectively reduce the loss of the tool and the workpiece, save economic and time costs, and thus provide intuitive data guidance for tool structure optimization and life evaluation, and provide an effective method for the design of high-performance cutting tools. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 is the microstructure and grain size of the tool material, among which, Figure 1 (a) shows the microstructure of three WC-Co cemented carbide samples. Figure 1 (b) in the figure shows the grain size distribution and average size.

[0047] Figure 2 is the degradation factor D H Relationship with temperature T.

[0048] Figure 3 Equivalent stress The calculation process of distribution.

[0049] Figure 4 is the equivalent stress on the tool surface Distribution calculation results, where Figure 4 (a) is the equivalent stress on the front cutting edge distributed, Figure 4 (b) is the equivalent stress on the back face of the tool distributed.

[0050] Figure 5 is the tool surface mean The calculation results are as follows: Figure 5 (a) is the mean value of the front cutting edge Figure 5 (b) is the mean value of the back face

[0051] Figure 6 is the tool surface mean Range analysis results, where Figure 6(a) is the mean value of the front cutting edge Range analysis, Figure 6 (b) is the mean value of the back face Range analysis.

[0052] Figure 7 Tool life in cutting experiments with tools of different structures. DETAILED DESCRIPTION

[0053] The present invention is described in detail below with reference to the accompanying drawings and embodiments.

[0054] The invention proposes a method for evaluating the structural applicability of a cemented carbide end mill based on tool material degradation, which comprises the following steps.

[0055] Step S01: preparing a cemented carbide sample and measuring the elastic modulus, Poisson's ratio, porosity, grain size, and friction coefficient material parameters of the tool material;

[0056] In one embodiment, the surface of the WC-Co cemented carbide is polished and observed by a scanning electron microscope (SEM). Based on the SEM image of the microstructure, the grain size of the material unit size of 4×4 μm (about 300 grains) is measured, and the average grain size is calculated.

[0057] The prepared WC-Co cemented carbide specimens have the following element proportions: 91.2wt% WC, 8wt% Co, 0.4wt% VC, and 0.4wt% Cr3C2, and the parameters such as the microstructure and material properties of the tool are identified.

[0058] The surfaces of three cemented carbide specimens were polished, and observation positions were randomly selected to obtain microstructure images, such as Figure 1 (a) is shown. Calculate the grain size distribution and average grain size, as shown in Figure 1 (b) is shown. The density of three samples was measured, the porosity was calculated and the average value was taken. Table 1 lists the mechanical properties parameters of the tool materials measured at room temperature.

[0059] Table 1 Cemented carbide parameters

[0060]

[0061] Step S02: Calculate the three-point bending elastic modulus; Calculate the three-point bending elastic modulus of the cemented carbide sample at high temperature;

[0062] The three-point bending test was carried out on the cemented carbide specimens at room temperature and high temperature to obtain the load and deflection before the specimens broke.

[0063] Calculate the three-point bending modulus of elasticity of the tool material.

[0064] Where L is the span of the specimen, F is the applied load, δ is the deflection of the specimen, and I is the bending moment of the specimen (I = bh 3 / 12, b is the width of the sample, h is the height of the sample.

[0065] High temperature three-point bending test was carried out on cemented carbide specimens, and the test parameters and results are listed in Table 2. As the temperature increases, the maximum load F before the material fracture gradually decreases, the deflection δ increases, and the deflection-load slope ΔF / Δδ decreases. The change of ΔF / Δδ reflects the degradation of tool material performance at high temperature.

[0066] Table 2 High temperature three-point bending test of cemented carbide

[0067]

[0068] Step S03: Calculate the degradation factor D of the cemented carbide tool material.

[0069] The relationship between tool cutting stress and tool material degradation is established. The influence of microstructure on tool material performance is represented by a continuous internal field, and the stress tensor of the material unit is:

[0070] σ=E(1-D)ε (1)

[0071] Among them, ε is the elastic strain of the material unit, E is the Young's modulus of the material, and D is the degradation factor.

[0072] When the tool material unit is subjected to compressive stresses σ1 and σ2, the axial and lateral strains ε1 and ε2 are:

[0073]

[0074] Among them, ε1 e and ε2 e is the elastic strain of the ideal material unit, ε1 d and ε2 d is the inelastic strain caused by microcrack growth, v is Poisson’s ratio, k = [(3-v) / (1+v)], M 11 、M 12 、M 21 and M 22 is a constant term, N = 4hbP / c 2 , P is the porosity, c=0.5d, d is the grain size of the material.

[0075] Under axial load pressure, formula (2) is simplified to:

[0076]

[0077] Constant M 11 and M 12 for:

[0078]

[0079] Where l is the crack extension length, θ = π / 4, w = 4c, μ is the friction coefficient, l * =0.27c,l ** =0.083c. In one embodiment, the stress tensor of the tool material unit containing micro-defects is:

[0080]

[0081] The stress tensor of an ideal tool material element is:

[0082]

[0083] From equations (1), (6) and (7), we can get:

[0084]

[0085] Initial degradation factor D of tool material I for:

[0086]

[0087] Initial degradation factor D I It is related to the microstructure and material parameters of the tool. Substituting the parameters in Table 1 into formula (9) to calculate the initial degradation factor D of the tool material I .

[0088] The three-point bending elastic modulus of cemented carbide is:

[0089]

[0090] Where L is the span of the specimen, F is the applied load, δ is the deflection of the specimen, and I is the bending moment of the specimen (I = bh 3 / 12, b is the width of the sample, h is the height of the sample).

[0091] According to the results in Table 2, the three-point bending elastic modulus of the tool material at different temperatures is calculated by formula (10), and the degradation factor D caused by high temperature is H for:

[0092]

[0093] Among them, D H is the high temperature degradation factor of cemented carbide at different temperatures, E b is the three-point bending elastic modulus of cemented carbide at room temperature (25°C), It is the three-point bending elastic modulus of cemented carbide at high temperature (300℃, 600℃ and 900℃).

[0094] like Figure 2 As shown, the high temperature degradation factor D H The relationship with temperature T is:

[0095] D H =f(T) (12)

[0096] Combined with initial degradation factor D I and high temperature factor D H , the comprehensive degradation factor D of the tool material is:

[0097] D=1-(1-D I )(1-D H ) (13)

[0098] Step S04: Considering the degradation of the tool material, calculate the effective stress component of the tool surface during cutting Equivalent stress

[0099] In the case of isotropic damage, when the stress components act on the same effective area, the effective stress components are:

[0100]

[0101] The equivalent stress of the damaged material element is:

[0102]

[0103] Among them: Among them, is the equivalent stress, is the effective stress component, σ ij is the ideal stress component, D is the degradation factor, h = 0.2, v is the Poisson's ratio, δ ij is the Kronecker symbol, is the hydrostatic stress, are matrices with the same subscripts as in the stress components.

[0104] Step S05: Design carbide end mills with different structural parameters and calculate the equivalent stress of different structural tools during cutting The evaluation index of the tool structure is obtained to evaluate the applicability of the tool structure.

[0105] The tool is a 2-edge integral end mill with a diameter of 5mm. Different side edge rake angles, side edge clearance angles, end edge clearance angles, and helix angles are selected to design L 16 (4 5 ) The four-factor four-level orthogonal table is shown in Table 3.

[0106] Table 3L 16 (4 5 )Orthogonal parameters

[0107]

[0108] The ideal stress component σ in formula (14) ij Calculated by finite element software AdvantEdge. The workpiece material is TC4 alloy and the tool material is WC-Co cemented carbide. The initial temperature of the workpiece and tool is 25°C. The cutting parameters are cutting speed 300m / min, feed per tooth 0.02mm / z, axial cutting depth 0.2mm and radial cutting depth 2.5mm. The cutting process is calculated using the Johnson-Cook model:

[0109]

[0110] Figure 3 is the equivalent stress under different tool structure parameters The calculation process. Extract the cutting temperature on the front and rear cutting edges and substitute it into equation (13) to calculate the degradation factor D. Substitute the degradation factor D and the stress component σ ij Substitute into equations (14) and (15) to calculate the stress component σ ij and equivalent stress Distribution and plotting of equivalent stress Distribution map. Figure 4 The calculated rake face and flank face distributed.

[0111] pass Figure 4 The results of calculating the average front and rear tool faces Values, such as Figure 5 shown.

[0112] right Figure 5 Analyze the data in and get the results of each factor at each level, such as Figure 6 As shown. The front cutting edge combination is determined to be A4B1C2D4, and the back cutting edge combination is determined to be A4B1C3D3. After comprehensive analysis, the combination is determined to be A4B1C2D4, that is, the side cutting edge angle γ s =12°, side edge clearance angle α s =8°, end edge clearance angle α e =10°, helix angle β=50°.

[0113] Step S06: Verify the correctness of the tool structure applicability evaluation method.

[0114] The tool structure (numbered OP) with the combination of A4B1C2D4, the parameters (3, 5, 8, 10, 11, 14) in Table 3 and the newly added parameters (Table 4) were selected to prepare the carbide end mill and conduct the cutting experiment. The parameters used in the cutting experiment are the same as those used in the above numerical calculation: 2-edge WC-Co carbide integral end mill (diameter 5mm), workpiece material titanium alloy TC4, cutting speed 300m / min, feed per tooth 0.02mm / z, axial cutting depth 0.2mm, radial cutting depth 2.5mm.

[0115] Table 4 Tool structure in cutting experiment

[0116]

[0117] Figure 7 The tool life of carbide end mills with different tool structures when cutting titanium alloy TC4. The cumulative cutting time of OP reaches 20.4 minutes. Except for the cumulative cutting time of tool No. 3, which is similar to OP, the life of other tools is lower than OP. The experimental results are consistent with the calculation results, which proves the accuracy and effectiveness of the carbide end mill structure applicability evaluation method based on tool material degradation of the present invention.

Claims

1. A method for evaluating the structural suitability of a cemented carbide end mill based on tool material degradation, characterized in that: The following steps are involved: Step S01: preparing a cemented carbide sample and measuring the elastic modulus, Poisson's ratio, porosity, grain size, and friction coefficient material parameters of the tool material; Step S02: Calculate the three-point bending elastic modulus; calculate the three-point bending elastic modulus of the cemented carbide sample at high temperature; perform three-point bending tests on the cemented carbide sample at room temperature and high temperature respectively, obtain the load and deflection before the sample breaks, and calculate the three-point bending elastic modulus of the tool material by the following formula: Where L is the span of the specimen, F is the applied load, δ is the deflection of the specimen, and I is the bending moment of the specimen (I = bh 3 / 12, b is the width of the sample, h is the height of the sample; Step S03: Calculate the degradation factor D of the cemented carbide tool material; Step S04: Considering the degradation of the tool material, calculate the effective stress component of the tool surface during cutting Equivalent stress Step S05: Design carbide end mills with different structural parameters and calculate the equivalent stress of different structural tools during cutting Obtain the evaluation index of the tool structure and evaluate the applicability of the tool structure; Step S06: Verify the correctness of the tool structure applicability evaluation method described in the above steps.

2. The method for evaluating the structural suitability of a cemented carbide end mill based on tool material degradation according to claim 1, characterized in that: In step S01, the surface of the WC-Co cemented carbide is polished and observed by a scanning electron microscope (SEM). Based on the SEM image of the microstructure, the grain size within the material unit size is measured and the average grain size is calculated.

3. The method for evaluating the structural suitability of a cemented carbide end mill based on tool material degradation according to claim 1, characterized in that: In step S03, the relationship between tool cutting stress and tool material degradation is established. The influence of microstructure on tool material performance is represented by a continuous internal field. The stress tensor of the material unit is: σ=E(1-D)ε Where ε is the elastic strain of the material unit, E is the Young's modulus of the material, and D is the degradation factor.

4. The method for evaluating the structural suitability of a cemented carbide end mill based on tool material degradation according to claim 3, characterized in that: When the tool material unit is subjected to compressive stresses σ1 and σ2, the axial and lateral strains ε1 and ε2 are: Among them, ε1 e and ε2 e is the elastic strain of the ideal material unit, ε1 d and ε2 d is the inelastic strain caused by microcrack growth, v is Poisson’s ratio, k = [(3-v) / (1+v)], M 11 、M 12 、M 21 and M 22 is a constant term, N = 4hbP / c 2 , P is the porosity, c = 0.5d, d is the grain size of the material, Under axial load pressure, the above formula is simplified to: Constant M 11 and M 12 for: Where l is the crack extension length, θ = π / 4, w = 4c, μ is the friction coefficient, l * =0.27c,l ** =0.083c.

5. The method for evaluating the structural suitability of a cemented carbide end mill based on tool material degradation according to claim 4, characterized in that: Substitute the tool material parameters obtained in step S01 into the following formula to calculate the initial degradation factor: D I : Where N is the number of cracks, N = 4hbP / c 2 ; P is porosity, E u =E / (1-2v);M 11 、M 12 is a constant term, including the Poisson's ratio, porosity, grain size, and friction coefficient parameters of the tool material. Establishing the high temperature degradation factor D H The relationship between the high temperature degradation factor D and the cutting temperature T is calculated by substituting the three-point bending elastic modulus obtained by Xing Hong in step S02 into the following formula: H : Among them, E b is the three-point bending elastic modulus of cemented carbide at room temperature, is the three-point bending elastic modulus of cemented carbide at different high temperatures; the high temperature degradation factor D is plotted H Relationship diagram with cutting temperature T, high temperature degradation factor D is obtained by least square method H Mathematical relationship with temperature T: D H =f(T) According to the initial degradation factor D I and high temperature degradation factor D H , the degradation factor of cemented carbide tool material is obtained by the following formula: D=1-(1-D I )(1-D H )。 6. The method for evaluating the structural suitability of a cemented carbide end mill based on tool material degradation according to claim 1, characterized in that: In step S04, the effective stress component of the tool surface cutting is calculated by combining the degradation factor D of the tool material with the following formula: Equivalent stress in, is the equivalent stress, is the effective stress component, σ ij is the ideal stress component, D is the degradation factor, h = 0.2, v is the Poisson's ratio, δ ij is the Kronecker symbol, is the hydrostatic stress, are matrices with the same subscripts as in the stress components.

7. The method for evaluating the structural suitability of a cemented carbide end mill based on tool material degradation according to claim 6, characterized in that: Ideal stress component σ ij The results are obtained by finite element method, as follows: the finite element software AdvantEdgeFEM is used to calculate the cutting process. The workpiece material is titanium alloy TC4, the tool material is WC-Co cemented carbide, and the tool is a 2-edge cemented carbide integral end mill. When the cutting edge achieves a complete cutting-in and cutting-out process, the cutting temperature T and the ideal stress component σ are extracted in the rake face and flank face areas. ij .

8. The method for evaluating the structural suitability of a cemented carbide end mill based on tool material degradation according to claim 1, characterized in that: In step S05, the side edge rake angle γ is selected. s 、 Side edge clearance angle α s , End edge rake angle γ e and helix angle β as tool structure parameters, design four factors and four levels L 16 (4 5 ) Orthogonal table, equivalent stress on the rake face and flank face of the tool cutting area Perform calculations.

9. The method for evaluating the structural suitability of a cemented carbide end mill based on tool material degradation according to claim 8, characterized in that: The parameters used in the calculation are: 2-edge carbide solid end mill, diameter 5mm, cutting speed 300m / min, feed per tooth 0.02mm / z, axial cutting depth 0.2mm and radial cutting depth 2.5mm.

10. The method for evaluating the structural suitability of a cemented carbide end mill based on tool material degradation according to claim 1, characterized in that: In step S06, the better tool structure obtained in step S05 is selected, and the cutting life is compared with other structural parameter tools. The cutting test parameters are the same as the calculation parameters. After cutting for a certain period of time, the wear width of the back tool face is measured. When the back tool face is severely worn or the tool is chipped, the experiment is stopped and the tool life of the tool is calculated.

Citation Information

Cited By

  • Hard alloy cutter life prediction and material selection method and system based on working condition parameters

    CN121245577A